THE IMPORTANCE OF GUIDANCE AND COUNSELING IN EFFECTIVE SCHOOL LEARNING - Charli Sitinjak; Zainab Canu (Jurnal Ilmiah Global Education, 2023)
Guidance and counselling are essential for a child's future success in school. The study acknowledges that counselling is a transformative process that assists people in learning everything they need to learn both inside and outside of school. Design / Methodology / Approach: Because this is an opinion paper, the study used to review research techniques. Findings: The paper acknowledges that counsellors must build the child's confidence in order for him or her to be able to provide the necessary information in order to help the child (students). Practical implications: Guidance counsellors should encourage students to attend therapy sessions to assist the child in their future success. Originality / Importance: This paper discusses the role of guidance and counselling in effective teaching and learning in schools for children's future success.